The concentrations of ambient Burkholderia pseudomallei during typhoon season in endemic area of melioidosis in Taiwan. - Ya-Lei Chen; Yu-Chuan Yen; Chun-Yuh Yang; Min Sheng Lee; Chi-Kung Ho; Kristina D Mena; Peng-Yau Wang; Pei-Shih Chen (Public Library of Science (PLoS), 2014)
BACKGROUND: Melioidosis is a severe bacterial infection caused by Burkholderia pseudomallei with a high case-fatality rate. Epidemiological and animal studies show the possibility of inhalation transmission. However, no B. pseudomallei concentrations in ambient air have been researched. Here, we developed a method to quantify ambient B. pseudomallei and then measured concentrations of ambient B. pseudomallei during the typhoon season and the non-typhoon season to determine the factors influencing ambient B. pseudomallei levels. METHODS: We quantified ambient B. pseudomallei by using a filter/real-time qPCR method in the Zoynan Region in Kaohsiung, southern Taiwan. Twenty-four hour samples were collected at a sampling rate of 20 L/min every day from June 11 to December 21, 2012 including during the typhoon season (June to September) and reference season (October to December). RESULTS: We successfully developed a filtration/real-time qPCR method to quantify ambient B. pseudomallei. To our knowledge, this is the first report describing concentrations of ambient B. pseudomallei. Ambient B. pseudomallei were only detected during the typhoon season when compared to the reference season. For the typhoons affecting the Zoynan Region, the positive rates of ambient B. pseudomallei were very high at 80% to 100%. During June to December, rainfall was positively correlated with ambient B. pseudomallei with a statistical significance. Sediment at a nearby pond significantly influenced the concentration of ambient B. pseudomallei. During the typhoon month, the typhoon was positively correlated with ambient B. pseudomallei whereas wind speed was reversely correlated with ambient B. pseudomallei. CONCLUSIONS: Our data suggest the possibility of transmission of B. pseudomallei via inhalation during the typhoon season.